The importance of determining the contiguous zone related to the authority of Indonesian Navy - Sirodjuddin; Made Warka; Slamet Suhartono; Sri Setyadji (Technium Social Sciences Journal, 2021)
This study uses normative research, using several approaches to statutory regulations, philosophical approaches and conceptual approaches. The contiguous zone doesn’t exceed 24 nautical miles from the baseline of the measured territorial sea width and the zone directly adjacent to the territorial sea of the country. This zone of the coastal state doesn’t have soverenitas as well as the territorial sea and the state can excercise certain powers. However, this zonal routeis considered important as a transition between the two parts of the sea. The authority of the coastal state can carry out the necessary oversight to protect violations of customs, fiscal, immigration of sanitary regulations within the territorial sea or the territorial sea and punish violations of these laws and regulations over it’s territory or territorial sea. The legal urgency of the contiguous zone regime, as stipulated in Article 33 UNCLOS 1982 states a demand for the state’s needs as the basis for law enforcement to see the benefits and strategic and economic value for the state. The consequence of ratifying UNCLOS 1982 means that the state submits itself to the provisions and obligations to follow up the various provisions contained therein. Manifesting in the form of national legislation as a measure to protect various interests of the state and guidance in law enforcement.